Parent-Child Relationship Quality and Family Transmission of Parent Posttraumatic Stress Disorder Symptoms and Child Externalizing and Internalizing Symptoms Following Fathers’ Combat-Trauma Exposure - Snyder, James (Dev Psychopathol, 2016)
Transactional cascades among child internalizing and externalizing symptoms, and fathers’ and mothers’ post-traumatic stress disorder symptoms were examined in a sample of families with a male parent who had been deployed to recent military conflicts in the Middle East. The role of parents’ positive engagement and coercive interaction with their child, and family members’ emotion regulation were tested as processes linking cascades of parent and child symptoms. A subsample of 183 families with deployed fathers and non-deployed mothers and their 4 to 13 year old children who participated in a randomized control trial intervention (After Deployment: Adaptive Parenting Tools, or ADAPT) were assessed at baseline prior to intervention, and at 12 and 24 months after baseline, using parent reports of their own and their child’s symptoms. Parents’ observed behavior during interaction with their children was coded using a multi-method approach at each assessment point. Reciprocal cascades among fathers’ and mothers’ PTSD symptoms, and child internalizing and externalizing symptoms were observed. Fathers’ and mothers’ positive engagement during parent-child interaction linked their PTSD symptoms and their child’s internalizing symptoms. Fathers’ and mothers’ coercive behavior toward their child linked their PTSD symptoms and their child’s externalizing symptoms. Each family members’ capacity for emotion regulation was associated with their adjustment problems at baseline. Implications for intervention, and for research using longitudinal models and a family-systems perspective of co-occurrence and cascades of symptoms across family members are described.